Mixing and mastering in the box : the guide to making great mixes and final masters on your computer - Savage, Steve, 1948- (2014)
"Mixing and mastering, the two final steps in the complex process of sound engineering, require both artistic finesse and technical facility. Even the slightest difference in the way a sound is processed can lead to a shift in the overall aesthetic of a piece, and so sound engineers must work towards an understanding of sound engineering that is particularly oriented towards the artistic and aesthetic. In order to create effective mixes, a sound engineer must maintain a distinct set of artistic goals while drawing on an in-depth understanding of the software involved in the process. Creating final masters requires specialized aural skills and a similarly advanced understanding of the software in order to fine-tune the product with respect to these goals. Mixing and Mastering in the Box addresses the practical and technological necessities of these two final steps without neglecting the creative process that is integral to the creation of high-quality recordings. Savage focuses primarily on creating mixes and masters in the Digital Audio Workstation (DAW), or "in the box," currently a popular platform in the field of sound engineering due to the creative advantages and advanced technological capabilities it offers to its users. However, much of the information presented in Mixing and Mastering in the Box is also applicable to analog mixing gear or a hybrid system of digital and analog tools. This book, which features over one hundred illustrations and a comprehensive companion website, is ideal for beginning or intermediate students in sound engineering with a focus on DAW, recording artists who do their own mixing and mastering, or musicians who wish to be better informed when collaborating on mixes and masters"--
Machine generated contents note: -- Contents -- Introduction -- Part I - Mixing & Mastering -- Introduction to Part I -- 1. The Starting Point -- 1.1 Preparing to mix and master -- 1.2 Where to mix and master -- 1.3 The tools of mixing and mastering -- 1.4 Introduction to the "Quick Guide" -- 2. Quick Guide to Great Mixes and Masters: Five best practices -- 2.1 Have a concept -- 2.2 Monitor level -- 2.3 Monitoring options -- 2.4 Revise, revise, revise -- 2.5 Live with your mix or master -- 3. Quick Guide to Great Mixes and Masters: Four common mistakes -- 3.1 Poor control of the low end -- 3.2 Overly bright mixes and masters -- 3.3 Overly compressed mixes and masters -- 3.4 Trusting inadequate monitoring -- Part II - Mixing -- Introduction to Part II -- 4. Building a Mix: The concepts and tools in detail -- 4.1 Starting concepts and setting level -- 4.2 Panning -- 4.3 Processing: EQ -- 4.4 Processing: Dynamics -- 4.5 Processing: Effects -- 4.6 Processing: What else is in the box? -- 4.7 The stereo buss -- 5. Automation and Recall: Fine-tuning -- 5.1 Online versus off-line automation -- 5.2 Details of online automation -- 5.3 Details of off-line automation -- 5.4 Timeline of automation -- 5.5 From simple to complex mixes -- 5.6 Fades -- 5.7 Advanced automation techniques -- 5.8 Recall -- 6. Mixing Piece by Piece: How to approach individual elements -- 6.1 Drums and percussion -- 6.2 Bass -- 6.3 Guitar -- 6.4 Keyboards -- 6.5 Vocals -- 6.6 Horns -- 6.7 Strings -- 7. Mix Collaboration: The mix team -- 7.1 How to communicate about mixes -- 7.2 Levels of mixer intervention -- 7.3 Managing remote mixing projects -- 8. Delivering Mixes: Formats, mix types and multiple mixes -- 8.1 Digital formats for mix delivery -- 8.2 Full mixes, TV mixes, and clips -- 8.3 Multiple versions of a single mix -- PART III - Mastering -- Introduction to part III -- 9. Setting Up to Master: Tools and files -- 9.1 Tools -- 9.2 Creating a template -- 9.3 Building the timeline -- 10. How to Listen for Mastering: From your ear to action -- 10.1 Level -- 10.2 Frequency/EQ -- 10.3 Dynamics and effects -- 10.4 Consistency -- 11. Creating a Master: The concepts and tools in detail -- 11.1 Creating a reference track -- 11.2 Processing: EQ -- 11.3 Processing: Level -- 11.4 Processing: Dynamics and effects -- 11.5 What else is in the box? -- 12. The Final Master: Creating and delivering -- 12.1 Creating a master -- 12.2 Formats and delivery options -- 13. Mastering Collaboration: The mastering team -- 13.1 How to talk about mastering -- 13.2 Levels of mastering intervention -- 13.3 Managing remote mastering projects -- Addendum I: Notes on surround mixing and mastering -- Addendum II: Why mixing and mastering can no longer be separated -- Index.
Includes bibliographical references and index.
Keywords: Sound -- Recording and reproducing -- Digital techniques; Mastering (Sound recordings); Sound recordings -- Remixing -- Data processing; Computer sound processing; Digital audio editors; MUSIC / Instruction & Study / General; MUSIC / Recording & Reproduction